PERUBAHAN SOSIAL MASYARAKAT ACEH JAYA PASCA GEMPA DAN TSUNAMI 2004 - Akmal Saputra (Prodi Sosiologi FISIP Universitas Teuku Umar, 2017)
This paper explains the social changes of Aceh Jaya society after the earthquake and tsunami 2004.This paper focuses on three things: changes in religious, social and cultural life as well as see the efforts of Aceh Jaya government in responding to the changes. The purpose of this research is to disclose the changes that occurred after the earthquake and tsunami which become the evaluation material for the policy maker and the planner of the community development program. The theory used in this research is the theory of social change. The method used in this research is qualitative method. Research findings indicate that there has been a change in the religious, social and cultural life of the Aceh Jaya community as a result of community development programs. Some of its development programs have an impact on people's non-self-reliance and some have been infiltrated by aqidah silting efforts which will then affect the religious life of the Aceh Jaya people. Changes in society also occur due to contact or interaction with different cultures that lasted for long periods of time. The Government of Aceh Jaya has made efforts to restore society to the expected conditions in accordance with the values prevailing in the Aceh Jaya society.Key Words: Community Development, Social Change